The Association of COVID-19 Risk Perception, County Death Rates, and Voluntary Health Behaviors among U.S. Adult Population - Elharake, Jad A (J Infect Dis, 2021)
The COVID-19 pandemic continues to adversely impact the United States (U.S.) socially, culturally, and economically. The purpose of this study was to understand the relationship between COVID-19 county death rates, risk perception, and U.S. adults’ voluntary behaviors—particularly physical distancing. Data were collected from CloudResearch/Qualtrics, Johns Hopkins University, the American Community Survey, and SafeGraph. Our results indicated that higher COVID-19 county death rates were associated with higher risk perceptions, leading to greater time spent at home. These findings will help public health officials identify strategies that best encourage voluntary health behaviors to help curb the spread of COVID-19.